2019
DOI: 10.3847/1538-4357/aaef30
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Major Solar Activity: Collisional Shearing between Nonconjugated Polarities of Multiple Bipoles Emerging within Active Regions

Abstract: Active Regions (ARs) that exhibit compact Polarity Inversion Lines (PILs) are known to be very flare-productive. However, the physical mechanisms behind this statistical inference have not been demonstrated conclusively. We show that such PILs can occur due to the collision between two emerging flux tubes nested within the same AR. In such multipolar ARs, the flux tubes may emerge simultaneously or sequentially, each initially producing a bipolar magnetic region (BMR) at the surface. During each flux tube's em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(118 citation statements)
references
References 114 publications
(169 reference statements)
10
108
0
Order By: Relevance
“…Fang and Fan, 2015;Takasao et al, 2015;Toriumi and Takasao, 2017;Cheung et al, 2019;Syntelis et al, 2019c). We note that the nature of shear and its role for the formation and eruption of MFRs has been investigated also in observational studies, for cases of two colliding emerging bipoles (Chintzoglou et al, 2019). Here we focus on the formation of MFRs in quadrupolar ARs in flux-emergence simulations.…”
Section: Mfr Formation Via Reconnectionmentioning
confidence: 92%
See 2 more Smart Citations
“…Fang and Fan, 2015;Takasao et al, 2015;Toriumi and Takasao, 2017;Cheung et al, 2019;Syntelis et al, 2019c). We note that the nature of shear and its role for the formation and eruption of MFRs has been investigated also in observational studies, for cases of two colliding emerging bipoles (Chintzoglou et al, 2019). Here we focus on the formation of MFRs in quadrupolar ARs in flux-emergence simulations.…”
Section: Mfr Formation Via Reconnectionmentioning
confidence: 92%
“…Flux emergence in multipolar ARs can eventually lead to the formation of MFRs (Chintzoglou et al, 2019). These authors reported observations of multiple bipoles, emerging either simultaneously or sequentially, in two emerging ARs.…”
Section: Flux Emergence Observationsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the k-scheme cannot determine the lead time between when the condition is first satisfied and the onset of the flare. It is likely that small-scale magnetic structures favorable for magnetic reconnection (18,24), flux emergence and cancellation (25,26), and the collision of nonconjugated magnetic polarities (27) may determine the initiation of the triggerreconnection.…”
mentioning
confidence: 99%
“…Their results revealed that large ARs with widespread and/or strong shearing flows along PILs tend to produce major flares within 24 hr. Furthermore, Chintzoglou et al (2019) demonstrated that the opposite polarities belonging to different bipolar magnetic regions collide, resulting in shearing and cancellation of magnetic flux, and named this kind of motion "collisional shearing". Fig.…”
Section: Photospheric Dynamicsmentioning
confidence: 99%